2011
DOI: 10.1002/ajmg.b.31248
|View full text |Cite
|
Sign up to set email alerts
|

GRIK4/KA1 protein expression in human brain and correlation with bipolar disorder risk variant status

Abstract: The kainate class of ionotropic glutamate receptors is involved in the regulation of neuronal transmission and synaptic plasticity. Previously we reported that a deletion variant within the gene GRIK4, which encodes the KA1 kainate receptor subunit, was associated with a reduced risk of bipolar disorder and increased GRIK4 mRNA abundance. Using a high resolution immunohistochemistry technique, we characterized KA1 protein localization in human brain and performed a genotype-protein expression correlation study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Conversely, increasing gene expression of Grik4 in the cortex and striatum increased anhedonic, anxiety, and depressive behaviors (Aller et al, 2015). These studies support human genetic studies that link variants in kainate receptor genes to bipolar disorder and schizophrenia (Knight et al, 2011; Pickard et al, 2008; Whalley et al, 2009). While these studies have been instructive in demonstrating a link to human disease, the dissection of the role of each of the subunits with a knockout approach has gone only part way to fully describing the roles of kainate receptors at synapses and their affects on behavior.…”
Section: Discussionsupporting
confidence: 78%
“…Conversely, increasing gene expression of Grik4 in the cortex and striatum increased anhedonic, anxiety, and depressive behaviors (Aller et al, 2015). These studies support human genetic studies that link variants in kainate receptor genes to bipolar disorder and schizophrenia (Knight et al, 2011; Pickard et al, 2008; Whalley et al, 2009). While these studies have been instructive in demonstrating a link to human disease, the dissection of the role of each of the subunits with a knockout approach has gone only part way to fully describing the roles of kainate receptors at synapses and their affects on behavior.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, genome-wide association studies support the role of GRIK4 as a risk factor for schizophrenia as well as bipolar disorder [94, 95]. A deletion variant within GRIK4 that caused increases in its mRNA expression and protein abundance has been found to be associated with a reduced risk of bipolar disorder [95, 96]. Complementing these data, GRIK4-knockout mice demonstrate impairments in pre-pulse inhibition, spatial memory acquisition and recall [97].…”
Section: Discussionmentioning
confidence: 98%
“…Human studies of carriers of the haplotype protective against bipolar disorder have found that there are increases in mRNA and GluK4 protein associated with the deletion variant [33, 34]. There are also several studies that have found reduced KAR expression in postmortem tissue from patients with schizophrenia [4244].…”
Section: Discussionmentioning
confidence: 99%
“…These studies identified a deletion variant in the 3′ untranslated region of GRIK4 in carriers of a haplotype that is protective against bipolar disorder [31]. In post-mortem hippocampal tissue from subjects carrying the deletion, mRNA transcripts and GluK4 protein levels are increased [33, 34]. In addition, imaging studies on healthy carriers of the protective haplotype demonstrated increased neural activity in the hippocampus during a face recognition task, demonstrating a functional effect of this genetic variation [35].…”
Section: Introductionmentioning
confidence: 99%